Investigating the Value of Counseling in Salala-Aisisagadai: A Local Wisdom Approach of Guidance and Counseling - Costa, Augusto da; Ximenes, Mateus De Jesus; Conceicão, Denata Viana da; Soares, Adelia; Conceicão, Jose da (Academia Edu Cendekia Indonesia (AEDUCIA), 2022)
Salala-Aisisagadai become a cultural dance (local wisdom) that involves many people beyond age and social status. What Salala-Aisisagadai? How it involves many people? Does it become an instrument of reconciliation? The objective of this research is to investigate the value of guidance and counseling in salala-aisisagadai. Researchers was utilizing the qualitative method in the ethnography approach. The informants are 5 traditional leaders of the Sirigiwari Clan. The approach to data collection is a semi-structured interview. Collected data was analyzed through the Milles method. The results of the study showed that the Salala-Asisagadai contains values of guidance and counseling, especially group counseling. Therefore Salala-Aisisagadai becomes a local wisdom of group guidance and counseling. The local community used this method in dealing with various experiences especially in expressing their sense of losing family members or loves ones.